Rancang Bangun Sistem Informasi Manajemen Aset Berbasis Web pada SMP Negeri 17 Tangerang Selatan - Yozan Dinata; Farizi Ilham; Naufal Alfi Rabani; Cintya Laura Melagro (CV. Shofanah Media Berkah, 2026)
Currently, the administration and management of goods at SMP Negeri 17 Tangerang Selatan still rely on conventional methods based on Microsoft Excel. This triggers various obstacles, ranging from the vulnerability of missing data, the length of time searching for information, to the ineffectiveness of staff performance. Therefore, this research focuses on building a web-based Asset Management Information System as a solution to these problems. The Waterfall approach was chosen as the software development method, supported by XAMPP, MySQL database, and the PHP programming language. The resulting application is equipped with various main modules, including goods data management, condition track records, borrowing circulation, maintenance history, and automatic report generation features. Based on the trial results, this platform has proven effective in reducing the risk of miscommunication between the Administration and Facilities divisions, while cutting the time for compiling data recapitulation to support the preparation for institutional accreditation.